LEGACY OF BLOOD - Knaak, Richard A. ([United States] : Blizzard Entertainment, 2017)
Since the beginning of time, the angelic hosts of the High Heavens and the demonic hordes of the Burning Hells have been locked in a struggle for the fate of all Creation. That struggle has now come to the mortal realm ... and neither Man nor Demon nor Angel will be left unscathed ... Norrec Vizharan has become a living nightmare. While on a quest to find magical treasure, the soldier of fortune discovers an artifact beyond his wildest dreams: the ancient armor of Bartuc, the legendary Warlord of Blood. But the mysterious armor soul. Now, pursued by demons who covet the dark armor for their own devices, Norrec must overcome a bloodlust he can scarcely control and learn the truth about his terrifying curse before he is lost to darkness forever ..
Keywords: Quests (Expeditions) -- Fiction; Demonology -- Fiction; Magic -- Fiction; Fantasy fiction